4-(4-Bromophenyl)-5-oxo-1,2,3,4,5,6,7,8-octahydroquinazoline-2-thione - Min Xie; Changquan Deng; Jie Zheng; Yulin Zhu (Acta Crystallographica Section E, 2009)
The title compound, C14H13BrN2OS, was synthesized from the multicomponent reaction between thiourea, 4-bromobenzaldehyde and cyclohexane-1,3-dione. The crystal packing is stabilized by intermolecular N—H...O, N—H...S, C—H...O and C—H...S hydrogen bonds. Br...O interactions [3.183 (3) Å] are also observed in the crystal structure.